Hashimoto's thyroiditis in childhood: presentation modes and evolution over time - De Luca Filippo; Santucci Simona; Corica Domenico; Pitrolo Elda; Romeo Marika; Aversa Tommaso (BMC, 2013)
Abstract Aim of this survey is to report the most recent views about Hashimoto's thyroiditis (HT) natural history according to the different presentations. In children presenting with either euthyroidism or subclinical hypothyroidism HT spontaneous course is frequently characterized by a trend towards deterioration of thyroid function, whereas in those presenting with overt hyperthyroidism a definitive resolution of hyperthyroid phase is to be expected. Another possible even though unusual outcome of HT is the conversion to Graves' disease.